Report of the Economic Programme Committee - Planning Commission (Planning Commission, 1948)
The Economic Programme Committee Report, presented to the All India Congress Committee (A.I.C.C.) in January 1948, laid down a comprehensive economic framework for India in the immediate post-independence period. Recognizing that political freedom required consolidation through social and economic transformation, the report emphasized the establishment of a democratic system rooted in social justice, equality, and improved living standards. It proposed a strategic national effort to double production within a decade, ensure full employment, and promote equitable distribution of income through structural reforms, including income ceilings and redistributive measures. In agriculture, the report advocated balanced and intensive cultivation, elimination of exploitative intermediaries, expansion of irrigation, and strengthened institutional finance through cooperative structures. Village and cottage industries were identified as vital instruments for rural employment and decentralized growth, with state support for research, training, and marketing. In the industrial sphere, the report recommended public ownership of key and monopolistic industries while fostering coordination between large-scale enterprises and small producers. The document strongly supported cooperative organization in production and distribution, encouraging consumer cooperatives to reduce middlemen influence and promote economic democracy. Worker participation in management, labor rights, and welfare measures were emphasized as essential components of industrial relations. To implement these measures effectively, the establishment of a permanent Central Planning Commission was proposed to guide taxation, foreign trade, and overall economic planning. Overall, the report articulated a vision of a self-reliant, decentralized, and socially equitable economy, integrating agriculture, industry, and community-based institutions to achieve balanced and inclusive national development.
Planning and Coordination Department Nagaland, Kohima December, 1977
Planning and Coordination Department Nagaland, Kohima December, 1977
Keywords: Economic Programme Committee Report; All India Congress Committee; Post-Independence Economic Policy; Social Justice; Full Employment; Agricultural Reform; Cooperative Societies; Cottage Industries; Public Ownership; Income Redistribution; Panchayati Raj